1974
DOI: 10.1007/bf01870189
|View full text |Cite
|
Sign up to set email alerts
|

Routes of nonelectrolyte permeation across epithelial membranes

Abstract: Summary. Radioactive tracer techniques were used to study the permeability of three epithelial membranes, the toad urinary bladder, frog choroid plexus, and rabbit gallbladder, to 16 nonelectrolytes. The general patterns of nonelectrolyte permeation were similar for all three membranes, and similar to those in other biological membranes. The permeability of lipophilic solutes was roughly proportional to their bulk phase oilJwater partition coefficients, but the slope was greater in the toad Nadder than in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
1

Year Published

1974
1974
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(55 citation statements)
references
References 43 publications
4
49
1
1
Order By: Relevance
“…However, phloretin has no effect on transpithelial water permeation across the toad bladder (22). In addition, urea permeability is inhibited by phloretin across the gall bladder (23).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, phloretin has no effect on transpithelial water permeation across the toad bladder (22). In addition, urea permeability is inhibited by phloretin across the gall bladder (23).…”
Section: Discussionmentioning
confidence: 93%
“…These findings would suggest that under certain circumstances the collecting duct is capable of active urea reabsorption. No mammalian renal studies have suggested active urea secretion; however, active urea secretion has been demonstrated by frog kidney (21), and carrier-mediated urea transport inhibited by phloretin has been shown in the toad bladder (22,23). However, phloretin has no effect on transpithelial water permeation across the toad bladder (22).…”
Section: Discussionmentioning
confidence: 99%
“…Compounds with five and six carbon atoms have o-A lying between 0-91 and 0-99. For all compounds tested -A is also plotted against molecular volume (Wright & Pietras 1974). For compounds with a molecular volume greater …”
Section: Dewhurst and Othersmentioning
confidence: 99%
“…via a transcellular pathway in the choroid plexus. Similarly, Wright & Pietras (1974) concluded that there is transcellular penetration of urea through the frog choroid plexus. Although it is not possible to distinguish between transcellular and paracellular routes (Smulders & Wright, 1971) on the basis of the half-time data, the relatively short half-time of 0 3 hr for the rate of appearance of tracer urea into the c.s.f.…”
Section: Permeability Of the Choroid Plexus To Ureamentioning
confidence: 99%